Inconsistent condom use between serodifferent sexual partnerships to the human immunodeficiency virus - Reis, Renata Karina (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2019)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: to analyze predictors of inconsistent condom use among HIV-positive people with sexual immunodeficiency virus serodifferent sexual partnership. METHOD: cross-sectional, analytical study with a consecutive non-probabilistic sample consisting of people living with the human immunodeficiency virus with serodifferent sexual partnership and who were in outpatient clinical follow-up. Data were collected through individual interviews guided by a semi-structured questionnaire and subsequently analyzed with bivariate analysis and logistic regression. RESULTS: Seven variables were independently associated with inconsistent condom use. Schooling less than 11 years of schooling (4.9 [2.4-10.1]), having multiple partnerships (5.0 [1.3-19.6]), using alcohol (2.1 [1.1 -4.4]) or other drugs (2.8 [1.2-6.3]), do not receive advice from a healthcare professional (2.0 [1.1-3.9]), have no knowledge of treatment as prevention (3.0 [1,2-6,9]) and not knowing that undetectable viral load reduces the risk of human immunodeficiency virus transmission (3.8 [1,1-13,7]) were predictors for inconsistent condom use. CONCLUSION: The study showed that psychosocial factors interfere with consistent condom use between serodifferent partnerships. Thus, it is highlighted that there is a need for comprehensive interventions that include the integration of clinical and psychosocial care.